2018
DOI: 10.1101/499384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AAV-mediated gene transfer restores a normal muscle transcriptome in a canine model of X-linked myotubular myopathy

Abstract: Multiple clinical trials employing recombinant adeno-associated viral (rAAV) vectors have been initiated for neuromuscular disorders, including Duchenne and limb-girdle muscular dystrophies, spinal muscular atrophy, and recently X-linked myotubular myopathy (XLMTM). Previous work from our laboratory on a canine model of XLMTM showed that a single rAAV8-cMTM1 systemic infusion corrects structural abnormalities within the muscle and restores contractile function, with affected dogs surviving more than four years… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 53 publications
5
8
0
Order By: Relevance
“…Mstn mRNA levels were previously shown to be reduced in skeletal muscles from XL-CNM mice and dogs. 3,33 In this study, we confirmed a reduction of myostatin at the mRNA level in muscle biopsies from XL-CNM mice and identified low levels of circulating myostatin in plasma. The shutdown of the myostatin pathway may be linked to a parallel increase in follistatin, an inhibitor of myostatin, and/or altered transcriptional regulation.…”
Section: Defects In the Myostatin Pathway In Xl-cnmsupporting
confidence: 77%
See 1 more Smart Citation
“…Mstn mRNA levels were previously shown to be reduced in skeletal muscles from XL-CNM mice and dogs. 3,33 In this study, we confirmed a reduction of myostatin at the mRNA level in muscle biopsies from XL-CNM mice and identified low levels of circulating myostatin in plasma. The shutdown of the myostatin pathway may be linked to a parallel increase in follistatin, an inhibitor of myostatin, and/or altered transcriptional regulation.…”
Section: Defects In the Myostatin Pathway In Xl-cnmsupporting
confidence: 77%
“…Therapeutic Dnm2 reduction resulted in a rapid increase in circulating myostatin, again supporting myostatin as a potential bloodbased biomarker for XL-CNM. An increase in Mstn mRNA was observed in several skeletal muscles, akin to previously published data testing another therapeutic approach in mice and dogs, 3,33 suggesting a possible molecular mechanism for increased plasma myostatin levels. These results suggest that circulating myostatin may be a relevant biomarker that may be used to monitor therapeutic efficacy in animal models of disease with different treatments.…”
Section: Circulating Myostatin As a Biomarker For Disease Severity And Therapy Efficacysupporting
confidence: 73%
“…The XLMTM Labrador/Beagles used in the present experiments were part of a previous gene therapy study [7,23]. Briefly, dogs were handled according to principles outlined in the National Institutes of Health (NIH) Guide for the Care and Use of Laboratory Animals.…”
Section: Canine Modelmentioning
confidence: 99%
“…However, these aspects so far neglected in XLMTM-related research may be of particular importance to the pathogenesis of this severe condition, considering that altered nuclear distribution may then be associated with aberrant global gene transcription (or synthetic activity), contractile protein content and overall muscle fibre dysfunction. In the current study, we first aimed to verify that hypothesis by using muscle tissue from humans with MTM1 mutations and animal models of XLMTM, including the Mtm1 knockout (KO) mouse, and the well-established canine colony with a mutation in MTM1 [ 1 , 5 7 , 9 , 13 , 23 , 38 ]. We also sought to investigate whether the presence of centrally located nuclei might directly interfere with muscle contraction, since these nuclei are buried between the contractile filaments.…”
Section: Introductionmentioning
confidence: 99%
“…A dose study carried out in the canine model established the dose-dependency of the therapy, with a significant correction achieved from 2 × 10 14 vg/kg, a quasi-normalisation of the phenotype at 5 × 10 14 vg/kg and no significant side-effects, apart from the expectable humoral immune response towards the vector and a thickening of the heart septal wall without functional consequences [ 244 ]. In this protocol, muscle expression defects evidenced by a transcriptomics approach were corrected by the mid-dose of 2 × 10 14 vg/kg [ 245 ]. Considering that the doses reversing the pathology are in the 10 14 vg/kg range and challenge vector production, an additional efficacy study was carried out in three infant NHPs [ 246 ].…”
Section: Translating Preclinical Studies Into Clinical Trialsmentioning
confidence: 99%